The effect of particle density on ultrasound-mediated transport of nanoparticles. (25th October 2016) - Lea-Banks, Harriet; Teo, Boon; Stride, Eleanor; Coussios, Constantin C
Abstract: A significant barrier to successful drug delivery is the limited penetration of nanoscale therapeutics beyond the vasculature. Building on recent in vivo findings in the context of cancer drug delivery, the current study investigates whether modification of nanoparticle drug-carriers to increase their density can be used to enhance their penetration into viscoelastic materials under ultrasound exposure. A computational model is first presented to predict the transport of identically sized nanoparticles of different densities in an ultrasonic field in the presence of an oscillating microbubble, by a combination of primary and secondary acoustic radiation forces, acoustic streaming and microstreaming. Experiments are then described in which near monodisperse (polydispersity index  <0.2) nanoparticles of approximate mean diameter 200 nm and densities ranging from 1.01 g cm −3 to 5.58 g cm −3 were fabricated and delivered to a tissue-mimicking material in the presence or absence of a microbubble ultrasound contrast agent, at ultrasound frequencies of 0.5 MHz and 1.6 MHz and a peak negative pressure of 1 MPa. Both the theoretical and experimental results confirm that denser particles exhibit significantly greater ultrasound-mediated transport than their lower density counterparts, indicating that density is a key consideration in the design of nanoscale therapeutics.